Energy Drink (Fearless) Effect on Sperm Parameters and Testicular Histology of Wistar rats (Journal of Experimental and Clinical Anatomy, 2024)
BACKGROUND AND AIM: In Nigeria, commercial energy drinks like Fearless are the most widely consumed. Nevertheless, there is currently no evidence linking the effects of Fearless energy drinks on seminal parameter. The purpose of this study was to investigate the effects of energy drinks like Fearless on the testis.METHODOLOGY: Twenty adult male Wistar rats weighing averagely 140-160g were divided into four groups of five rats each. Group A was the control and received 5ml/kg of distilled water. For three weeks, the following doses of the Fearless energy drink was given to groups B, C, and D via oral gavage: 2.5, 5, and 7.5 mL/kg/day, respectively. After treatment, the animals' were sacrificed and their testis were weighed. The sperm parameters (motility, count) were evaluated, and the testis were processed for histological studies.RESULTS: Results showed that there was a statistically significant decrease (p < 0.05) in the sperm count and motility in the ED (Fearless) groups (Group B 619±65.76 and 69.5±2.5, Group C 602±70.01 and 62.0±10.00, Group D 514±26.5 and 55.0±.6.19) respectively when compared to group A (662±10.01 and 92.5±2.5). There was an increase in the body weight in the treated groups, but no difference was observed with respect to relative weights of the testis. Groups B and C showed moderate effect on the testicular tissue with moderate spermatogenic arrest. Group D, exhibited scattered appearance of seminiferous tubules with loss of spermatogenic germ cells, marked degeneration of interstitial cells and congested thick vessels in the interstitial tissue.CONCLUSION: Fearless energy drink induced dose dependent negative changes on sperm quality and morphology of the testis .of Wistar rats